NEW APPROACHES IN THE TREATMENT OF METABOLIC DISORDERS IN LIVER FAILURE (World Bulletin of Public Health, 2024)
Hepatotoxicity is damage caused by exposure to a drug or nonpharmacological agents. Risk factors include: individual intolerance, age, gender, alcohol consumption, smoking, concomitant use of other drugs, liver disease, genetic and environmental factors. [1–3] Although most lipophilic drugs can cause hepatotoxicity , [4] antibiotics, nonsteroidal anti-inflammatory drugs (NSAIDs), and anticonvulsants are the pharmacological groups that are the most common causes. [1, 5-9]. Among the drugs administered intravenously, antibiotics and neoplasia drugs are mostly associated with liver toxicity
Keywords: Hepatotoxicity; intolerance; age; gender